Pengaruh Terapi Kombinasi Ekstrak Etanol Mentimun (Cucumis sativus) dan Vildagliptin terhadap Penurunan Kadar Glukosa Darah Tikus Wistar yang Diinduksi Aloksan (The Effect of Combination Treatment of Cucumber (Cucumis sativus) Ethanolic Extract and Vilda - Chita Setya Widyani; Sugiyanta Sugiyanta; Kristianningrum Dian Sofiana (Pustaka Kesehatan, 2015)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Effective management is needed. Cucumber is one of traditional medicine contains saponins with antihyperglycemic effects. This study aimed to determine the differences between combination therapy of cucumber ethanolic extract and vildagliptin and monotherapy of cucumber ethanolic extract or vildagliptin to decrease the blood glucose. The rats were injected with alloxan 125 mg/kgBW. There were 5 groups: K1 was normal group, K2 was a group of diabetic rats without treatment, K3 was a group of diabetic rats with cucumber ethanolic extract (200 mg/kgBW), K4 was a group of diabetic rats with vildagliptin treatment (1,8 mg/200 gBW), K5 was a group of diabetic rats with combination treatment of cucumber ethanolic extract (200 mg/kgBW) and vildagliptin (1,8mg/200 gBW). After 14 days, fasting blood glucose (FBG) was measured. The result showed that the mean FBG after treatment (FBG 2) of K1, K2, K3, K4, and K5 were (82,4; 277,2; 188,2; 199,2; 180,6) mg/dL, respectively. In conclusion, the potential of cucumber ethanolic extract and vildagliptin in combination treatment was more effective to decrease the blood glucose levels than both monotherapy of cucumber ethanolic extract or vildagliptin in Wistar rats.   Keywords: Diabetes Mellitus, Cucumber, Vildagliptin, Blood Glucose Levels, Alloxan